Purifikasi Biogas Sistem Kontinyu Menggunakan Zeolit - Sugiarto, Sugiarto; Oerbandono, Tjuk; Widhiyanuriyawan, Denny; Permana Putra, Faruq Syah (Jurnal Rekayasa Mesin, 2013)
The continued development of the technology industry and the rapid depletion of petroleum energy the need for alternative sources of renewable energy to be a very important consideration. Biogas is a renewable energy that has great potential as an alternative energy. The content consists of CH4 biogas as fuel around 50-80% and CO2 as an impurity around 27-45%. With the CO2 gas can affect the purity of CH4 in biogas womb. Therefore, to get the maximum quality of biogas purification necessary. The research was done by making purification equipment (purifier) with zeolite granular solid filler mounted on a biogas digester system continue. Purification processes varying on zeolite layer that fills the purifier is 1, 2, 3, 4, and 5 layer. All walks take a purification process for 60 minutes and observed every 15 minutes. The results showed that the increasing time between biogas purification with zeolite, the CO2 levels tend to decline with the lowest percentage of 21.3% and CH4 levels increase with the highest percentage of 74.7%. This is due to the increasing time of purification, CO2 absorbed in the zeolite structure more and more. So with the absorption of CO2 by the zeolite, the resulting levels of CH4 has increased. In addition to the greater number of zeolite layers become increasingly declining CO2 and CH4 levels increase. This is because the more the number of layers of filler, wide contact area between the biogas by zeolite increasingly large that CO2 is absorbed by the zeolite increased.Keywords: Zeolite, CO2, CH4, purification, biogas continuous system